2011
DOI: 10.1111/j.1748-0361.2011.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sleep Duration and Depressive Symptoms in Rural Communities of Missouri, Tennessee, and Arkansas

Abstract: Purpose To determine the association between sleep duration and depressive symptoms in a rural setting. Methods We conducted a cross-sectional study using data from Wave 3 of the Walk the Ozarks to Wellness Project including 12 rural communities in Missouri, Arkansas, and Tennessee (N = 1,204). Sleep duration was defined based on average weeknight and weekend hours per day: short (< 7), optimal (7-8), and long (> 8). The primary outcome was self-reported elevated depressive symptoms. Multivariable logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
3
23
0
1
Order By: Relevance
“…Poor sleep is an important etiology of depression (Chang et al, 2012; Paunio et al, 2014). This observation is in agreement with our finding that participants with short sleep durations had higher likelihood of developing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep is an important etiology of depression (Chang et al, 2012; Paunio et al, 2014). This observation is in agreement with our finding that participants with short sleep durations had higher likelihood of developing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…77,79,80,85 Short self-reported sleep duration is associated with increased cross-sectional and longitudinal risk for depression, whether measured as symptoms or as a diagnosis. 77,[79][80][81][82][83][84]86 The threshold for short sleep varies across studies from 5-7 hours, with the majority using 6 hours. Some data also demonstrate increased risk associated with sleep duration longer than 8-9 hours.…”
Section: Mental Healthmentioning
confidence: 99%
“…The studies in this area focus on the change in sleep duration between race, ethnic groups and regional differences . It can also be said that sleep duration is a feature that may vary due to population structure and urban/rural environment . Hale and Doindicated in their study that blacks and some other racial minorities as Hispanics (excluding Mexican Americans) and non‐Hispanic “Others” were related to increased risk of short sleeping.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep duration change in urban environments depends on stressors, neighborhood, living environment and structural conditions. It has been reported that in rural areas, the average sleep time is less than 7 h and short sleep duration increases the risks of depression and obesity …”
Section: Introductionmentioning
confidence: 99%